Sustentabilidade do microcrédito : uma análise da experiência do Banese - Daltro, Hércules Silva (2010)
One of the biggest challenges faced by the Brazilian government and society is the establishment of policies aimed at the promotion of economic and social developments taking into consideration the probability of having new vacancies and the increase of salaries poorer populations may have. The micro and small businesses became the principal shelter for the unemployed population and their financial sustainability essentially depends on the credit the traditional bank institutions will make available, what may not occur due to the fact that these entrepreneurs normally work in the informality and do not fulfill the requirements demanded by the banking loans. Based on this scenery, the microcredit has to be considered as the inductor of a credit policy highlighted by the usage of a specific methodology (loans, credit agent and other ones), aimed at the distribution of credit resources to this segment. This study evaluates the microcredit sustainability through the analyses of the experience of Banese Microcredit, relating the human development rate, segregated in the income rate (IDHMIncome) in a sample of cities, with the generated wealth and the amount of credit which is made available. The hypothesis which directed this study was formulated aimed at the searching of evidences in the literature, in the experience of institutions and in studies made by specialized consultancy, taking the methodological dimension of auto sustainability of microcredit organizations, with the adoption of sustainability and profitability and quality, efficiency and productivity indicators. The observed results highlighted the fact that in certain cities with low IDHM-Incomes there is a stronger necessity for a more prominent action from the bank in terms of credit concession.